When past and future meet in architecture teaching: heritage and GIS - Santos, Bertha (2020)
This article aims to present some of the teaching methodologies applied in the Integrated Master degree in Architecture at the University of Beira Interior, Covilhã (Portugal). The discussion focuses on the collaborative and interdisciplinary approach adopted for the teaching/learning process, particularly the courses of History of Portuguese Architecture, Project III and Geographical Information Systems (GIS), all belonging to the 3rd year. The aim of this approach is to encourage project-based learning through the use of spatial tools and new technologies to analyse and manage architectural spatially referenced data. As students present a heterogeneous level of general History knowledge and of History of Portuguese Architecture in particular, it was necessary to introduce the acquisition of knowledge to achieve the required competence on scientific work, research, adequate scientific terminology and architectural dating to finally achieve the expected results. Interdisciplinary state of the art and knowledge gathering performed by the students concerned Architecture, GIS, Civil Engineering, Heritage, and History. Consequently, an interdisciplinary connection was achieved during student research of religious Portuguese heritage in Covilhã by implementing a GIS based inventory and analysis. Concerning the curricular unit of Project III, design studies aiming to evaluate the potentialities of a site are developed based on requests from external institutions. These requests are incorporated in the course program on an annual basis, adapted accordingly to the defined skills to be achieved. For students this is an important experience as they must respond to a real design problem. The conjugation with the GIS curriculum complements all the necessary study for a better understanding of the site and its surroundings, thus developing a useful spatial database for future reference. This collaboration with the GIS curricular unit began in 2016/2017 with Project III and evolved in 2017/2018 to History of Portuguese Architecture through practical works gathering knowledge from multiple subjects. Regarding the experience of teachers and students, the use of GIS in Architecture has proven to be a success, given students’ skills on the use of new technologies. This also allows them to contact with other scientific, technical and technological realities, preparing students for a demanding international work context.